2013
DOI: 10.1111/ajps.12060
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Proximity: Examining the Effects of Protests on Political Attitudes

Abstract: This article utilizes data from the Latino National Survey (2006) to analyze temporal and spatial variation in the effects of the immigrant rights marches in 2006 on Latino attitudes towards trust in government and self‐efficacy. Using a unique protest dataset, we examine the effects of proximity and scale by mapping respondents’ specific geographic location against the location of the marches as well as size of the protests using Geographic Information Systems (GIS). We find that local proximity to small marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 57 publications
2
67
0
3
Order By: Relevance
“…Delimiting the boundaries at 30 days and 100 miles allows for meaningful variation while still conforming measuring exposure in terms of space and time in a theoretically sound way. Moreover, the specificity of these measures far exceeds standard measures of time and space and is consistent with prior work in this area (see Wallace et al., ).…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Delimiting the boundaries at 30 days and 100 miles allows for meaningful variation while still conforming measuring exposure in terms of space and time in a theoretically sound way. Moreover, the specificity of these measures far exceeds standard measures of time and space and is consistent with prior work in this area (see Wallace et al., ).…”
supporting
confidence: 86%
“…For example, examing Latino public opinion before, during, and after the protest wave, Silber Mohamed () found that the demonstrations bolstered Latinos’ sense of American identity and panethnicity, while Zepeda‐Millán and Wallace's () study revealed that Latino perceptions of racial identity increased during and after the protests compared to before they began. Similarly, very little prior work examines the spatial dimensions of the protests and how proximity influenced Latino public opinion (see, however, Wallace, Zepeda‐Millán, and Jones Correa, ; Carey et al., ).…”
Section: Time Space and The Effects Of Protests On Public Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether there is a relationship between the protests and Latino racial identity is an important question to examine because most research looking into the empirical effects of the rallies on Latino public opinion have focused on questions such as how Latinos viewed the demonstrations and why those who took part in the marches did so (Pallares and Flores-Gonzalez 2008;); what impacts the protests had on feelings of Latino panethnicity (Mohamed 2013); and what effects the series of demonstrations had on Latino political efficacy and trust in government (Pedraza, Segura, and Bowler 2011;Wallace, Zepeda-Millán, and Jones Correa, Forthcoming). Yet, with the exception of Wallace, Zepeda-Millán, and Jones Correa (Forthcoming) and Mohamed (2013), 5 studies that focus on the relationship between the marches and Latino political attitudes are limited in that the data they utilize are drawn from a single point in time, either from surveys undertaken during the demonstrations or after the protest wave had subsided (Suro and Escobar 2006;Pedraza, Segura, and Bowler 2011).…”
Section: Racialization In Actionmentioning
confidence: 99%
“…More recently, there has been an important attempt to address this empirical and theoretical blind‐spot. A significant number of scholars have stressed the centrality of urban environments in shaping the political incorporation of immigrants (Bloemraad, ; Varsanyi, ; de Graauw et al ., ; Steil and Vasi, ; Wallace et al ., ). De Graauw et al .…”
Section: Introductionmentioning
confidence: 97%